Synthesis of axially Schiff base new substituted silicon phthalocyanines and investigation of photochemical and sono-photochemical properties - Unlu, Seda; Elmali, Fikriye Tuncel; Atmaca, Goknur Yasa; Erdogmus, Ali (ELSEVIER, 2022)
Sono-photodynamic therapy, which show a very high therapeutic effect compared to photodynamic therapy, is a newer method for anticancer treatments. However, unlike Photodynamic therapy (PDT), the number of studies measuring the efficiency of singlet oxygen for the Sono-photodynamic therapy (SPDT) method is quite insufficient in the literature. Therefore, this study aimed to synthesis novel axially substituted silicon (IV) phthalocyanines containing imine groups with improved photochemical properties and then reported the efficiency of singlet oxygen by both of photochemical and sono-photochemical studies. According to the results, the substituent group increased the singlet oxygen yield of silicon (IV) phthalocyanine dichloride and the sonophotochemical effect increased the singlet oxygen yields (Phi(Delta)=0.35 for 2a, 0.69 for 2b in photochemical study, 0.78 for 2a, 0.97 for 2b in sono-photochemical study).This article may pave the way to achieve high singlet oxygen efficiency.
Keywords: Sono-photodynamic therapy; Silicon phthalocyanine; Photodynamic therapy; Singlet oxygen; Schiff base; RECENT PROGRESS; CANCER; ZINC; Oncology